2021
DOI: 10.2196/22406
|View full text |Cite
|
Sign up to set email alerts
|

Administering Virtual Reality Therapy to Manage Behavioral and Psychological Symptoms in Patients With Dementia Admitted to an Acute Care Hospital: Results of a Pilot Study

Abstract: Background As virtual reality (VR) technologies become increasingly accessible and affordable, clinicians are eager to try VR therapy as a novel means to manage behavioral and psychological symptoms of dementia, which are exacerbated during acute care hospitalization, with the goal of reducing the use of antipsychotics, sedatives, and physical restraints associated with negative adverse effects, increased length of stay, and caregiver burden. To date, no evaluations of immersive VR therapy have bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…In terms of acceptability, our findings mirror what was reported in previous studies with similar populations; newer models of VR headsets (i.e., Oculus Go) are feasible for use with older adults with dementia (including moderate and severe cognitive impairment) who exhibit responsive behaviors (Appel et al, 2021d;Brimelow et al, 2020). Feedback regarding the comfort of the HMD was generally positive, however, some aspects can be improved/customized to suit the unique needs of this population.…”
Section: Frontiers Insupporting
confidence: 85%
“…In terms of acceptability, our findings mirror what was reported in previous studies with similar populations; newer models of VR headsets (i.e., Oculus Go) are feasible for use with older adults with dementia (including moderate and severe cognitive impairment) who exhibit responsive behaviors (Appel et al, 2021d;Brimelow et al, 2020). Feedback regarding the comfort of the HMD was generally positive, however, some aspects can be improved/customized to suit the unique needs of this population.…”
Section: Frontiers Insupporting
confidence: 85%
“…22 We recently conducted a randomized controlled trial at an acute care hospital, evaluating the effects of VR on BPSD including the need for sitters (people who provide supervision of challenging patients), refusal of care, and use of drugs. 23,24 We found that VR-therapy had a statistically significant effect on reducing the cluster of "aggressiveness" as well as trended towards reducing length of stay.…”
Section: Emotional Changesmentioning
confidence: 79%
“…In older adult populations, VR has been explored as a means to conduct cognitive training, activities of daily living (ADL) exercises, physical rehabilitation exercises, falls prevention exercises, screen for mild cognitive impairment, as well as engage, relieve stress, and improve QoL (Snowdon, 1997;Beason-Held et al, 2013;D'Cunha et al, 2019;Liu et al, 2019;Phu et al, 2019;Clay et al, 2020;Matsangidou et al, 2020). More recently, VR has been suggested as a means to manage BPSDs in people with dementia, with some early studies showing promising results Appel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%